VELOCITY OF SOUND IN THE ARABIAN SEA ALONG THE SOUTH MALABAR COAST DURING THE POST-MONSOON SEASON - Sastry, A A Rama; Ramamirtham, C P (Indian Journal of Fisheries, 2016)
THE knowledge of the sound distribution in the sea is of importance infathmetry and in sonar studies. It is with a view to find the correctionsto various echo-sounders with different 'sounding velocities' for use in theArabian Sea, along the South-Western coast of India, this study has beenundertaken. As a preliminary, the results for the period immediately afterthe South-West monsoon only, are given in this paper. As it would be ofinterest for further studies in locating the subsurface barriers by sonic methodand because of the importance of the sound velocity in under-water acoustics,the distribution of sound velocity is fully discussed without making anyspecial reference to the individual problems.